Perbandingan Kecepatan Gabungan Algoritma Quick Sort dan Merge Sort dengan Insertion Sort, Bubble Sort dan Selection Sort - Muhammad Ezar Al Rivan (Jurnal Teknik Informatika dan Sistem Informasi, 2017)
Ordering is one of the process done before doing data processing. The sorting algorithm has its own strengths and weaknesses. By taking strengths of each algorithm then combined can be a better algorithm. Quick Sort and Merge Sort are algorithms that divide the data into parts and each part divide again into sub-section until one element. Usually one element join with others and then sorted by. In this experiment data divide into parts that have size not more than threshold. This part then sorted by Insertion Sort, Bubble Sort and Selection Sort. This replacement process can be reduce time used to divide data into one element. Data size and data type may affect time so this experiment use 5 data sizes and 3 types of data. The algorithm dominates in experiment are Merge-Insertion Sort and Merge-Selection Sort.